Human Resource Excellence : An Assessment of Strategies and Trends - Lawler, Edward E.; Boudreau, John W. (Stanford, CA : Stanford University Press, 2020)
As a field, human resources has been slow to evolve, despite a great need and opportunity for change. Human Resource Excellence delivers the newest findings about what makes HR successful and how it can add value to today's organizations. Tracing changes in a global sample of firms across the US, Europe, and Asia, this landmark volume provides an international benchmark against which to measure a company's HR practice. For over twenty years, USC's Center for Effective Organizations has conducted the definitive longitudinal study of the human resource management function. Analyzing new data every three years, the Center charts changes in HR and offers guidance on how human resource professionals can drive firm performance. In this latest survey, Edward E. Lawler III and John W. Boudreau conclude that HR is most powerful when it plays a strategic role, makes use of information technology, and has tangible metrics and analytics. Their insights offer an essential understanding of HR's changing role in strategy, big data, social and knowledge networks, and the gig economy.
Frontmatter -- CONTENTS -- TABLES AND FIGURES -- PREFACE AND ACKNOWLEDGMENTS -- THE AUTHORS -- CHAPTER 1. What HR Needs to Do -- CHAPTER 2. What HR Does -- CHAPTER 3. The Strategic Role of HR -- CHAPTER 4. HR Decision Science -- CHAPTER 5. HR Organization and HR Skills -- CHAPTER 6. Measuring Efficiency, Effectiveness, and Impact -- CHAPTER 7. The Results of HR Metrics and Analytics -- CHAPTER 8. Information Technology in HR -- CHAPTER 9. The Effectiveness of HR -- CHAPTER 10. Determinants of HR Effectiveness -- CHAPTER 11. Determinants of Organizational Performance -- CHAPTER 12. How HR Has Changed -- CHAPTER 13. What the Future of HR Should Be -- REFERENCES -- APPENDIX A. Research Partners -- APPENDIX B. Research Design -- APPENDIX C. 2016 HR Global Study: U.S. Results (N = 114)
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Jul 2020)
Keywords: Organizational effectiveness; Personnel management; change; human resources; management; metrics; organizational effectiveness; strategy; talent; BUSINESS & ECONOMICS / Human Resources & Personnel Management